Structural hybridization as a facile approach to new drug candidates. Issue 23 (1st December 2020) - Sampath Kumar, Halmuthur M.; Herrmann, Lars; Tsogoeva, Svetlana B.
Graphical abstract: Abstract: Structural hybridization of preclinically and clinically validated pharmacologically active molecules has emerged as a promising tool to develop new generations of safe and highly efficient drug candidates against various diseases including microbial infections, virus infections and cancer. Strategies of drug-drug combinations have been adopted to generate hybrid conjugates of many clinically used drugs, designed to address inherent problems associated with these drugs. Thus, the design of hybrids was aimed to achieve higher efficacy through possible multi-target interactions, selective delivery of the drug to the site of action with the aim to improve bioavailability, alleviate toxicity and circumvent drug resistances. In this review article, we summarize the progress made in recent years in the rapidly growing field of drug discovery, focusing on the rationality of the hybrid design with particular emphasis on the linker architecture, which plays a crucial role in the overall success of a hybrid drug.